The Impact of MSME’s Development of Halal Products On Sustainable Livelihood - Muhaimin, Rizal; Sudrajat, Anton; Rokhlinasari, Sri (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Islam 45, 2025)
The development of Micro, Small and Medium Enterprises (MSMEs) based on halal products has a very significant role in encouraging economic growth in rural areas. The existence of MSMEs not only creates jobs and increases community income, but also contributes to creating an economic system that is inclusive, sustainable, and based on sharia values. In this context, the concept of sustainable livelihoods is a relevant strategic approach to understand the contribution of halal products to sustainability in the economic, social and environmental dimensions. This study specifically highlights the potential and role of halal MSMEs developing in Mertapada Kulon Village, Cirebon Regency. This village has great potential in local economic development, but there is still a gap in research related to how halal MSMEs can have an impact on the sustainable livelihoods of local communities. The purpose of this study is to analyze the development strategy of halal product MSMEs and evaluate the extent of their impact on the achievement of Sustainable Livelihood indicators. This research uses qualitative methods with data collection through in-depth interviews and direct observation. The results showed that the halal MSME development strategy has a positive impact on rural economic development. This is reflected in increased household income, improved community welfare, decreased levels of economic vulnerability, and the fulfillment of life needs in a more decent and sustainable manner.